1998
DOI: 10.1002/(sici)1097-0215(19980529)76:5<749::aid-ijc21>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

HT-1080 fibrosarcoma cell matrix degradation and invasion are inhibited by the matrix-associated serine protease inhibitor TFPI-2/33 kDa MSPI

Abstract: The urokinase‐urokinase receptor system plays a dominant role in the degradation and invasion of extracellular matrix (ECM) by tumor cells. In this system, urokinase bound to its cell receptor converts plasminogen to plasmin, a broad‐spectrum serine protease that participates in the degradation and invasion of connective tissues by tumor cells. In this study, we evaluated whether these activities of plasmin are inhibited by a newly characterized human 32 kDa recombinant serine protease inhibitor called trypsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 32 publications
(36 reference statements)
5
51
1
Order By: Relevance
“…3B). The presence of TFPI-2 in the ECM of MEG-01 cells is consistent with the earlier data obtained using ECM from different cell types (6,23,27).…”
Section: Expression Of Tfpi-2 and Cd41 By Meg-01 Cells And Bonesupporting
confidence: 91%
See 2 more Smart Citations
“…3B). The presence of TFPI-2 in the ECM of MEG-01 cells is consistent with the earlier data obtained using ECM from different cell types (6,23,27).…”
Section: Expression Of Tfpi-2 and Cd41 By Meg-01 Cells And Bonesupporting
confidence: 91%
“…The role of TFPI-2 in regulating ECM turnover and tumor invasion has been well documented and reviewed (8,9,27,30). However, whether or not TFPI-2 plays a role in regulating blood coagulation and/or fibrinolysis remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an ECM-associated serine protease inhibitor (Rao et al, 1996). A previous study of recombinant TFPI-2 showed that TFPI-2 inhibited the generation of plasmin at the surfaces of ECM and HT-1080 ®brosarcoma cells and inhibited the degradation and invasion of matrix by these cells (Rao et al, 1998). TFPI-2 directly inhibits plasmin, thereby releasing growth factors from ECM and activating transforming growth factor b and certain pro-MMPs by tumor cells, which causes degradation of ECM followed by invasion (Kwaan, 1992;Rao et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The TFPI-2 gene has been mapped to chromosome 7q22 by¯uoresence in situ hybridization (Miyagi et al, 1996b). Recombinant TFPI-2 inhibited plasmin, regardless of whether the enzyme was associated with tumor cells or with ECM, and inhibited matrix degradation and Matrigel invasion by HT-1080 ®brosarcoma cells (Rao et al, 1998).…”
mentioning
confidence: 99%